The Effect of CdCl2 and annealing treatments on structural properties of CdS/CdTe heterojunction - Razooqi, Muhammad A. (Iraqi Journal of Physics, 2011)
CdS and CdTe thin films were thermally deposited onto glass substrate. The CdCl2 layer was deposited onto CdS surface. These followed by annealing for different duration times to modify the surface and interface of the junction. The diffraction patterns showed that the intensity of the peaks increased with the CdCl2/annealed treatment, and the grain sizes are increased after CdCl2/annealed treatment